Acoustic microscopy characterization of highly-ordered anodized nanoporous alumina films for nanotechnology applications - Dubey, Pooja; Declercq, Nico F.; Zhai, Min; Locquet, Alexandre; Jung, Mi; Woo, Deokha; Citrin, D. S. (Elsevier, 2023)
The acoustic properties of a well-aligned nanoporous alumina (NP Al2O3) film synthesized through a two-step anodization process have been characterized nondestructively using scanning acoustic microscopy (SAM). A novel method is proposed to extract the material properties of thin nanoporous film such as Elastic modulus, Poison's ratio, thickness, and porosity. The proposed technique to obtain the material properties is based on leaky surface-acoustic waves. These investigated material properties also agree well with their corresponding standard values obtained by other methods. An additional experimental investigation is conducted to detect nonuniformity in NP Al2O3 films based on the V(z) curve. It is found that the Rayleigh velocity for various scanning areas shows variation corresponding to non-uniformity in the film. This non-uniform surface morphology of nanoporous Al2O3 is also validated by polarized-resolved terahertz time-domain spectroscopy (THz TDS). A further thickness measurement using THz TDS coupled with acoustic microscopy provides a complete characterization of the NP Al2O3 film.